Media Landscape on Tumblr: News organization convergence attributes in youth-oriented social media networks. Issue 6 (17th August 2016) - Kilgo, Danielle K.
Abstract : Growing concern for the future news consumption of young people and millennials has left journalism scholars and educators with the interesting challenge of engaging youth in news. Rendered "newsless" by one Pew Research report, this study examines news organizations' publication practices in the largely under-researched and youth-oriented social network Tumblr. Results suggest that while news organizations have become increasingly involved in social media networks, many have created a digital presence on Tumblr and failed to maintain their accounts. Of the few that do consistently post, content appears to be tailored to adhere to the culture of the Tumblr platform, and posts are diversified in terms of format and topic. Surprisingly, though the majority of Tumblr users are considered to be young people and young adults, audience activity totals indicate that user interests may stretch beyond entertainment, widening assumptions that youth are primarily interested in entertainment, sports, and trivial news.